1997
DOI: 10.1021/jp972143m
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Nitrosyl Chloride (NOCl) by Aqueous Solutions

Abstract: The uptake kinetics of nitrosyl chloride (NOCl) by aqueous solutions has been measured as a function of temperature, using two different techniques, i.e., the wetted-wall at atmospheric and reduced pressure and the droplet train flow tubes, both techniques being combined with FTIR and HPLC detection. Uptake coefficients, which were shown to be slightly temperature dependent, range from 0.012 to 0.0058 for temperatures between 273 and 293 K. The production of HONO was observed from the hydrolysis of NOCl, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…This heterogeneous activation mechanism was originally proposed and investigated by Finlayson-Pitts et al (1989) and confirmed in an aerosol smog chamber by Zetzsch and Behnke (1992) and Behnke et al (1993Behnke et al ( , 1997 Thornton et al (2010) and over continental Europe (Phillips et al, 2012). A further important class of heterogeneous reactions provides chloride to the aqueous phase example such as the well-known conversion of molecular chlorine to bromine on halide 5 surfaces: One example is the well-known conversion of molecular chlorine to bromine on halide surfaces:…”
Section: Interactive Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This heterogeneous activation mechanism was originally proposed and investigated by Finlayson-Pitts et al (1989) and confirmed in an aerosol smog chamber by Zetzsch and Behnke (1992) and Behnke et al (1993Behnke et al ( , 1997 Thornton et al (2010) and over continental Europe (Phillips et al, 2012). A further important class of heterogeneous reactions provides chloride to the aqueous phase example such as the well-known conversion of molecular chlorine to bromine on halide 5 surfaces: One example is the well-known conversion of molecular chlorine to bromine on halide surfaces:…”
Section: Interactive Discussionsupporting
confidence: 55%
“…Br 2 Cl − (aq) → Br 2 + Cl − (aq) (R22) 10 and the formation of HONO from an uptake of NOCl into the aqueous phase (Scheer et al, 1997):…”
Section: Interactive Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also notable that separate experiments (see SI Text) show that water vapor does not enhance the heterogeneous hydrolysis of ClNO in this system. This suggests that under some conditions, loss of ClNO to aerosol particles and surfaces at the terrestrial-air interface may be much slower than what is expected to occur in bulk water (28,29). Fig.…”
Section: ]mentioning
confidence: 94%
“…54 In the presence of O 3 (leading to N 2 O 5 from NO X ), ClNO 2 could be formed 53 that is more stable against hydrolysis 18 and can be photolyzed to form Cl and NO 2 (J ClNO2 = 2 × 10 −4 s −1 ). This summarizes the activation of Cl via uptake of, for example, NO 2 , N 2 O 5 , and O 3 on the deliquesced salt, and concomitant release of photolyzable precursors.…”
Section: Resultsmentioning
confidence: 99%